Level Keterbacaan Buku Teks Bahasa Indonesia: Analysis Faktor Gender - Iin Nur Yasinta; Muhammad Saleh; Usman Usman (Nuances of Indonesian Language, 2021)
Research purpose to: (1) describe the readability of the Indonesian textbooks Curriculum 2013 for male students of class VIII; (2) describing the readability of Indonesian textbooks Curriculum 2013 for female students of class VIII; (3) describe the differences in the readability of the Indonesian textbooks Curriculum 2013 in male and female students of class VIII.This type of research is quantitative research. The sample used in this study was grade VIII as many as 62 students. 25 male students and 33 female students. Determination of the sample is done by total sampling technique. The instrument in this study was a cloze test. Data analysis techniques used statistical analysis of independent sample t-test. The results of the study concluded: (1) the level of readability of the Indonesian textbooks Curriculum 2013 for male students of class VIII are categorized as difficult or low (frustation) on all texts tested, with the percentage of respondens in exposition text (88.9%), explanatory text (77.8%), review texts (100%), persuasive texts (95.6%), and nonfiction texts (95.24%). (2) Level of readability of Indonesian textbooks Curriculum 2013 for female students of class VIII are categorized as difficult or low (frustation) on all texts tested, with the percentage of respondens in exposition text (56.3%), explanatory text (59.4%), review text (88.23) %), persuasive texts (64.7%), and nonfiction texts (86.2%). (3) Based on the statistical test results obtained significance value of the review text 0.015, persuasive text with a significance value of 0.004, and nonfiction text with a significance value of 0.005. This shows that there are significant differences in the level of readability of Indonesian textbooks Curriculum 2013 for male and female students of class VIII in the review text, persuasive text, and nonfiction text. As for the text that does not have significant differences, namely exposition text and explanatory text.Keywords: readability, textbooks, gender